STATUS KEBERLANJUTAN BUDIDAYA RUMPUT LAUT DI NEGERI SAWAI KECAMATAN SERAM UTARA KABUPATEN MALUKU TENGAH - Tuhumury, Semuel Frederik; Bachmid, Miarah; Sangaji, Masudin (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2019)
Seaweed cultivation activities in the Sawai Village, District of North Seram, Central Maluku Regency has been known since 1994, but has not seen a significant development until now. For it is necessary to study the sustainability status of seaweed cultivation as a whole through the five dimensions of the ecological, economic, technological, social and institutional in order to get a clear condition of seaweed cultivation. This study aims to determine the condition of seaweed cultivation in the Sawai Village, to analyze the status and sustainability indexes seaweed cultivation activities of the five dimensions of sustainability and to formulate the direction of the management of its seaweed cultivation. This research was conducted in December 2016-February 2017 in Sawai Village. The method were used in this research is descriptive qualitative. The data were used a primary and a secondary data. The results showed that the condition of the aquatic environment, the emploiment, marketing, post-harvest handling, and which system maintenance seaweed in Sawai village supports the development of seaweed, so the opportunity to be developed as a central potential of seaweed farming. The level of sustainability of seaweed cultivation in the Sawai village, are in the category of less sustainable. ecological dimension (83.77%) are in continuous status, the economic dimension (47.81%) the technological dimension (34.26%), the social dimension (46.97%) and institutional dimension (32.84%) are in status less sustainable. There are eight directions of management that could be recommended for the development of seaweed cultivation in the Sawai Village. ABSTRAK Kegiatan budidaya rumput laut di Negeri Sawai, Kecamatan Seram Utara, Kabupaten Maluku Tengah telah dikenal sejak tahun 1994, namun belum terlihat perkembangan yang signifikan hingga sekarang. Untuk itu perlu dikaji status keberlanjutan budidaya rumput laut secara menyeluruh melalui lima dimensi yaitu dimensi ekologi, ekonomi, teknologi, sosial dan kelembagaan agar mendapatkan gambaran yang jelas mengenai kondisi budidaya rumput laut di Negeri Sawai. Penelitian ini bertujuan untuk mengetahui kondisi budidaya rumput laut di Negeri Sawai, menganalisis status dan indeks keberlanjutan kegiatan budidaya rumput laut dari lima dimensi keberlanjutan serta merumuskan arahan pengelolaan budidaya rumput laut di Negeri Sawai. Penelitian ini dilaksanakan pada bulan Desember 2016-Februari 2017 dengan menggunakan metode deskriptif kualitatif. Menggunakan data primer maupun sekunder. Hasil penelitian menunjukkan kondisi lingkungan perairan, serapan tenaga kerja, pemasaran, penanganan pasca panen, dan sistem pemeliharaan rumput laut di Negeri Sawai mendukung pengembangan rumput laut, sehingga berpeluang untuk dikembangkan sebagai sentral budidaya rumput laut potensial. Tingkat keberlanjutan budidaya rumput laut di Negeri Sawai, berada dalam kategori kurang berkelanjutan. Dimensi ekologi (83,77%) berada pada status berkelanjutan, dimensi ekonomi (47,81%) dimensi teknologi (34,26%), dimensi sosial (46,97%) dan dimensi kelembagaan (32,84%) berada pada status kurang berkelanjutan. Terdapat delapan arahan pengelolaan yang dapat direkomendasikan untuk pengembangan budidaya rumput laut di Negeri Sawai. Kata Kunci : Status keberlanjutan, budidaya, rumput laut, pengelolaan, Negeri Sawai